A New Species of Elianella Vercammen-Grandjean (Trombidiformes: Trombiculidae) from the Insular Equatorial Guinea with a Key to the Species into this Genus - Bassini-Silva, Ricardo (2021)
Purpose: The African continent has 452 chiggers (Trombidiformes: Trombiculidae) in 61 genera. One of these, Elianella Vercammen-Grandjean, 1956, has only two species known for Africa. The objective of the present study is to describe a new species for Equatorial Guinea, with the aim of increasing knowledge so scarce for Africa. Methods: In this study, we provide drawings, measurements and microscopy images on a Microscope Zeiss for the new species described below. Also, this type of the new species is deposited in the USNM. Results: We describe a new species of Elianella collected parasitizing the Bioko Forest Shrew, Sylvisorex isabellae Heim de Balsac (Eulipotyphla: Soricidae) from the insular Equatorial Guinea. Also, we are providing a key for the three species of Elianella. Conclusion: Finally, we are contributing to the knowledge of African species, due the fact this new species is the first chigger recorded to the Equatorial Guinea, on the west coast of Central Africa.